Experiência intercultural mediada pela internet: o ensino de línguas via telecolaboração - Lima, Bruno Ferreira de (2017)
This work aims to promote an intercultural experience via asynchronous telecolaboration in the school environment. There are also specific objectives in this research, which are to elaborate and implement a protocol of preparatory activities for the asynchronous telecolaboration and to identify aspects that denote the development of the Intercultural Communicative Competence (ICC) in the productions of the participating Brazilian students. Based on this, we carried out a qualitative interpretative research (BORTONI-RICARDO, 2008) that counted on the participation of 30 Brazilian High School students from IFRN Campus Natal Zona Norte, who corresponded via e-mail with about 110 university students from the University of California - Davis for six weeks. The corpus analyzed was composed of a questionnaire applied to the Brazilian students as part of their preparation for the telecolaboration, and by e-mails written by them during the weeks of the partnership. We are support the studies of Byram (1997, 2008) and Kramsch (1993, 1996, 1998), regarding the development of Intercultural Communicative Competence, intercultural language teaching and the relationship between language and culture; In Belz (2003), Menard-Warwick et al (2013) and O'Dowd (2003; 2011) who discuss telecolaboration as a resource for language teaching. The results show that the Brazilian students took advantage of the intercultural experience to discuss complex subjects such as prejudice, cultural diversity and the notions linked to the English language in Brazil. The activity protocol proved to be consistent in preparing students for the collaboration. In the list of actions developed and implemented, we highlight the simulations of sending and replying to messages and the exhibition of real emails for discussing grammatical correction, the adequacy of levels of formality and addressing cultural aspects. In addition, through the linguistic analysis applied to the e-mails, in which the Appraisal Systems were used, the indicators of the development of all the components of the ICC, namely, attitude, knowledge, skills and critical cultural awareness were evidenced.